First Report of Tomato chlorosis virus in China - Zhao, R N (Plant disease, 2013)
In October 2012, a severe yellowing disease was found on greenhouse and plastic house tomato (Solanum lycopersicum) plants in Beijing, China. The disease incidence varied from 5 to 80% in each of six fields across Haidian and Daxing districts. The lower leaves showed symptoms of interveinal chlorosis, leaf brittleness, and limited brown necrotic flecks, similar to symptoms induced by Tomato chlorosis virus (ToCV) and Tomato infectious chlorosis virus (TICV) (two members of genus Crinivirus, family Closteroviridae) (4). A large number of whiteflies (Bemisia tabaci) were also observed. Leaf samples were taken from eight symptomatic and two asymptomatic tomato plants in two plastic houses in the Haidian district and total RNA was isolated from the 10 samples using TRIzol reagent (Tiangen, Beijing, China). Nested reverse transcription (RT)-PCR was performed to test the presence of ToCV and TICV with degenerate primers HS-11 and HS-12 and specific primers ToC-5/ToC-6 or TIC-3/TIC-4 for ToCV or TICV, respectively (1). With ToCV primers, a 463-bp specific fragment was amplified from eight symptomatic samples but not from two asymptomatic samples, and there was no amplification with TICV primers from any sample. Sequence analysis of the amplified fragment showed 99% nucleotide sequence identity with the heat shock protein 70 homolog (HSP70h) gene of ToCV isolates from Japan (GenBank Accession No. AB513442), Spain (DQ136146), Florida (AY903448), and Greece (EU284744). The presence of ToCV was confirmed by amplification of a 848-bp fragment covering the coat protein (CP) gene of ToCV with primers CP-F (5'-GAATCTTTTAGAAGCTTTGGTTTAAGG-3') and CP-R (5'-GATCCTCTTGATCCTCATAGATTTC-3') (3). The CP had 97 to 99% amino acid sequence identity to the above-mentioned four ToCV isolates. A sequence of the CP gene obtained from one isolate was deposited at GenBank (KC311375). Additionally, virions were isolated from 25 g of symptomatic samples followed Klaassen's method (2) and their lengths were estimated to be about 800 to 850 nm by transmission electronic microscopy To our knowledge, this is the first report of ToCV on tomato in mainland China. Tomato is one of the most widely cultivated crops in China and the spread of ToCV in China may cause significant economic losses. Further information on the prevalence and incidence of ToCV is required to assess the potential impact of this virus. References: (1) C. I. Dovas et al. Plant Dis. 86:1345, 2002. (2) V. A. Klaassen et al. J. Gen. Virol. 75:1525, 1994. (3) H. Tomoki et al. J. Gen. Plant Pathol. 76:168, 2010. (4) G. C. Wisler et al. Phytopathology 88:402, 1998